2022
DOI: 10.1085/jgp.202113027
|View full text |Cite
|
Sign up to set email alerts
|

Gating and anion selectivity are reciprocally regulated in TMEM16A (ANO1)

Abstract: Numerous essential physiological processes depend on the TMEM16A-mediated Ca2+-activated chloride fluxes. Extensive structure–function studies have helped to elucidate the Ca2+ gating mechanism of TMEM16A, revealing a Ca2+-sensing element close to the anion pore that alters conduction. However, substrate selection and the substrate–gating relationship in TMEM16A remain less explored. Here, we study the gating–permeant anion relationship on mouse TMEM16A expressed in HEK 293 cells using electrophysiological rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Our results also found that the free energy reduces from T 1 to the open state I 2 (Figure B), which suggests that I 2 is a stable state. When the Cl – ion reaches T 2 , the anion is surrounded by a local negatively electrostatic environment that is mainly induced by pore-lining E624 (located in the loop connecting α5 and α6 helixes) and E633 (located in the α6 helix) in the extracellular vestibule (Figure S4), despite the extracellular vestibule mainly providing a positively electrostatic environment that makes favorable contributions to chloride conduction. , The changes in electrostatic environments for chloride conduction from I 2 to T 2 account for the small barrier of I 2 –T 2 in Figure B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also found that the free energy reduces from T 1 to the open state I 2 (Figure B), which suggests that I 2 is a stable state. When the Cl – ion reaches T 2 , the anion is surrounded by a local negatively electrostatic environment that is mainly induced by pore-lining E624 (located in the loop connecting α5 and α6 helixes) and E633 (located in the α6 helix) in the extracellular vestibule (Figure S4), despite the extracellular vestibule mainly providing a positively electrostatic environment that makes favorable contributions to chloride conduction. , The changes in electrostatic environments for chloride conduction from I 2 to T 2 account for the small barrier of I 2 –T 2 in Figure B.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings on the electrostatic potential distribution also support this point. Besides, we found that the Cl – ion in the T 1 state is in a strongly negatively charged environment formed by Ca 2+ binding sites ,, (Figure A). The electrostatic repulsion of the Cl – ion and the negatively charged environment hinder the movement of anions.…”
Section: Resultsmentioning
confidence: 99%
“…Complete activation of TMEM16A occurs when the concentration of intracellular calcium ([Ca 2+ ]i) surpasses 1.5 µM (6)(7)(8)(9)(10)(11). Channel´s activity is modulated by intra-and extracellular protons (12)(13)(14)(15) and the permeating anion, which seems to couple the gating and permeation processes (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%